Assignment Model in Inclusive Education in Forming Tolerance Attitude at Pondok Modern Darussalam Gontor - Syarifah; Maskuri; Junaidi Mistar; Ihwan Mahmudi; Abu Darda (Institute for Islamic Studies and Aswaja (LPIK) of Universitas Islam Malang, 2026)
This study aims to describe the assignment model in inclusive education as an effort to foster tolerance at the Pondok Modern Darussalam Gontor. Using a qualitative ethnographic approach, the study was conducted through observation, interviews, and documentation over a one-year period. The results indicate that tolerance education at Gontor is implemented through two main models: direct tolerance education, which emphasizes cross-group interaction between students, and indirect tolerance education, which focuses on developing an open personality toward differences. The assignment model is an integral part of leadership education, where students are given various tasks that require responsibility, collaboration, and initiative in organizations and social activities. Through assignments, students learn to lead, cooperate, and manage their time, thus fostering active and passive tolerance in the daily life of the Islamic boarding school. This model has proven effective in developing the character of students who are tolerant, disciplined, and ready to live in a pluralistic society.